2015
DOI: 10.1126/sciadv.1500470
|View full text |Cite
|
Sign up to set email alerts
|

High-precision geochronology confirms voluminous magmatism before, during, and after Earth’s most severe extinction

Abstract: High-precision geochronology confirms voluminous magmatism before, during, and after Earth’s most severe mass extinction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
368
1
4

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(386 citation statements)
references
References 47 publications
13
368
1
4
Order By: Relevance
“…SLIP activity was reported to have lasted ∼300 ky, before and concurrent with the P-Tr mass extinction, and continuing for at least 500 ky after extinction cessation (3). This age model agrees with the magmatism of the SLIP representing a trigger for the P-Tr mass extinction; within this time span there is a clear temporal link between the emplacement of NiS ore-bearing intrusions in the SLIP, starting at 251.907 ± 0.094 Ma, and the onset of extinction (3).…”
supporting
confidence: 84%
“…SLIP activity was reported to have lasted ∼300 ky, before and concurrent with the P-Tr mass extinction, and continuing for at least 500 ky after extinction cessation (3). This age model agrees with the magmatism of the SLIP representing a trigger for the P-Tr mass extinction; within this time span there is a clear temporal link between the emplacement of NiS ore-bearing intrusions in the SLIP, starting at 251.907 ± 0.094 Ma, and the onset of extinction (3).…”
supporting
confidence: 84%
“…We found that nickel concentrations increase abruptly just before the blowup. Moreover, subsequent dating of Siberian nickel deposits confirms that nickel-rich lavas erupted prior to the extinction [2].…”
mentioning
confidence: 79%
“…Recently, an additional piece of the puzzle fell into place. Massive Siberian volcanism, long thought to coincide roughly with the extinction, is now known to have preceded it and continued beyond it [2].…”
mentioning
confidence: 99%
“…A major rise in global average temperature of ~15 °C occurred at this time, leading to the greatest mass extinction recorded (Sun et al, 2012). This event has been linked to major eruptions and gas release in the Siberian Traps large igneous province (Svensen et al, 2009;Reichow et al, 2009;Burgess and Bowring, 2015).…”
Section: Geological Backgroundmentioning
confidence: 97%
“…A possible explanation for the sudden influx close to Fennoscandia and Greenland is tectonic uplift associated with rifting along the Norway-Greenland margin (e.g., Müller et al, 2005), possibly in the form of rift shoulder uplift. The progradation of the large, Uralian-derived easterly system was likely related to tectonism coincident with and caused by the main phase of volcanism of the Siberian Traps (Burgess and Bowring, 2015), as the Uralian orogeny was in a waning phase at this stage (Puchkov, 2009). This likely led to large-scale uplift and erosion of the Uralian orogen, and to vastly increased sediment supply in the Early Triassic and deposition of coarsegrained fluvial deposits in the Uralian foreland basin (Puchkov, 2009;Reichow et al, 2009).…”
Section: Mechanism For Sudden Sediment Influx After the Permian-triasmentioning
confidence: 99%